(untitled) - Lloyd, G. E. R. (Cambridge, 2002)
In The Ambitions of Curiosity one of the world's foremost philosophers of science takes a wider canvas than conventional histories of science and investigates the origins of systematic inquiry in science, historiography and the study of language itself. Focussing on Greece, China, and Mesopotamia, Geoffrey Lloyd shows how research developed differently in those ancient societies and examines why. He illustrates the unexpected results of many research efforts, the tensions between state control and individual innovation and the different ways those tensions were resolved--problems that remain central to science today.
Keywords: Science, Ancient,Science,Science,Khoa học, cổ đại,Khoa học, cổ đại; Greece,China,Hy Lạp,Trung Quốc